The sacralized power of the clerics of Castile (13th and early 14th centuries) - Teodoro, Leandro Alves [UNESP] (Univ Federal Rio Grande Sul, Programa Pos-graduacao & Historia, 2019)
From the first half of the thirteenth century, there was an emergence of works written in Castilian language destined to regulate the functions attributed to the diocesan clergy of the Crown of Castile. By serializing books in verse, synod constitutions and other texts focused on the basic formation of clerics, elaborated between the thirteenth and fourteenth centuries, this study aims to examine the promotion of the power of Eucharist consecration and the instructional role of the Mass celebration at a time when the pastoral action of Iberian bishops and the expansion of the attributes of the parish churches were strengthened. In other words, the aim of this work is to analyze the measures adopted by great ecclesiastical authorities regarding the sacralization of speeches and gestures of clerics ordained during that period.
Keywords: Crown of Castile; Sacrament of the Eucharist; Diocesan clergy; 13th and 14th centuries